Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Test - Page 750: 19



Work Step by Step

$(\sqrt 5+5)(\sqrt 5-5)$ =$\sqrt 5(\sqrt 5-5)+5(\sqrt 5-5)$ =$\sqrt 5\sqrt 5-5\sqrt 5+5\sqrt 5-25$ =$(\sqrt 5)^{2}-5\sqrt 5+5\sqrt 5-25$ =$(\sqrt 5)^{2}-25$ =$5-25$ =$-20$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.